Kepemimpinan Politik dalam Perspektif Islam - Solihin, Muhtar (Jurnal Review Politik, 2016)
An effort to separate religion from social and political role just goes on to explain that religion is private matter of human or it was an individual moral teaching. Religion is not a rule of organization, society and state, such as regulations for leadership, economic, social systems and so on. The view of secularism, which is the capitalist mainstream does not appear applying to Islam, because Islam still has tawâzun (balance) framework. One of the proofs of tawâzun, for example, is about political leadership which in Islamic perspective is in the corridor of muamalah, especially human relations with each other. For this reason, the author is interested in presenting a political leadership discourse in Islamic perspective.